The Soviet High Command, 1967-1989 : Personalities and Politics. - Herspring, Dale R. (Dale Roy) (Princeton legacy library., 2014)
The recent transformations in the USSR are nowhere more evident than in the Soviet military. Top-level military officers have been relieved of their positions, Gorbachev has warned of lean times for the military, the symbolic role of the armed forces has been downgraded, and the concept of ""military sufficiency"" points to major modifications in Soviet force structure. Contrary to some who see Gorbachev as a Sir Galahad out to slay the evil military high command, Dale Herspring concludes that the relationship between the highest Soviet political and military leaders is at the moment more s